Laparoscopic 5-mm port site hernia: a rare but preventable complication of laparoscopy - Ramesh, B.; Kurkuri, Shraddha Neminath; Metgud, Satwik Basavaraj (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
The port site hernia (PSH) is a rare but potentially dangerous complication of laparoscopic surgery ranging from early small omental herniation to delayed hernia formation with or without bowel entrapment. Though 5 mm PSH is a rarer entity compared to 10 mm PSH, it is a completely preventable cause of morbidity. The aim of this article is to emphasize the importance of fascial closure of trocar site including peritoneum in order to significantly reduce postoperative morbidity as well as to know the importance of early diagnosis to avoid serious subsequent events, in all 10 mm or larger ports and a few exceptional cases of 5 mm ports also.